2013
DOI: 10.1074/mcp.m112.024307
|View full text |Cite
|
Sign up to set email alerts
|

The Proteomic Investigation of Chromatin Functional Domains Reveals Novel Synergisms among Distinct Heterochromatin Components

Abstract: Chromatin is a highly dynamic, well-structured nucleoprotein complex of DNA and proteins that controls virtually all DNA transactions. Chromatin dynamicity is regulated at specific loci by the presence of various associated proteins, histones, post-translational modifications, histone variants, and DNA methylation. Until now the characterization of the proteomic component of chromatin domains has been held back by the challenge of enriching distinguishable, homogeneous regions for subsequent mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 106 publications
(118 reference statements)
3
67
0
Order By: Relevance
“…The mESC chromatin proteomic profiling data produced a catalog of chromatin-associated proteins, which includes a large number of known and candidate chromatin regulators and transcriptional regulators. Our results overlap and confirm chromatin-associated proteins identified in other MS studies (8,12) but also provide a larger catalog of chromatin proteins associated with a larger variety of chromatin types. We confirmed that several of the candidates (PHIP, UBR7, USP48, and PUS7) were indeed associated with appropriate histone-marked segments of the genome as detected by chromatin proteomic profiling.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The mESC chromatin proteomic profiling data produced a catalog of chromatin-associated proteins, which includes a large number of known and candidate chromatin regulators and transcriptional regulators. Our results overlap and confirm chromatin-associated proteins identified in other MS studies (8,12) but also provide a larger catalog of chromatin proteins associated with a larger variety of chromatin types. We confirmed that several of the candidates (PHIP, UBR7, USP48, and PUS7) were indeed associated with appropriate histone-marked segments of the genome as detected by chromatin proteomic profiling.…”
Section: Discussionsupporting
confidence: 89%
“…Mass spectrometry (MS) can identify large populations of proteins present in specific preparations (8-10) but does not reveal how these proteins occupy specific portions of the genome. A recently developed approach combined ChIP with MS (ChIP-MS) to identify protein complexes that are associated with other proteins known to occupy sites in the genome (11)(12)(13). Here we adapt this approach to profile the proteins associated with chromatin containing specific histone modifications across the genome of mouse embryonic stem cells (mESCs).…”
mentioning
confidence: 99%
“…The minimum score required for the phosphorylation site was 30 to obtain reliable results. Protein phosphorylation was quantified using the peptideextracted ion chromatograms embedded in MaxQuant (22). Student's t test was used for statistical comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, D 3 -acetylation offers two additional advantages that facilitate the discernment of isobaric modified peptides: first, the alkylation occurs only on unmodified and mono-methylated lysines, but not on di-and tri-methylated residues; as such modified peptides bearing the same total number of modifications but in different arrangements are differentially decorated by distinct set of D 3 -acetyl groups that produce unambiguous m/z shifts. Second, distinct patterns of D 3 -alkylation cause slightly different retention times in liquid chromatography on reverse phase column, which generate an additional level of separation for isobaric modified peptides 21 .…”
Section: Representative Resultsmentioning
confidence: 99%